A Single Assistive Profile Applied by a Passive Hip Flexion Device Can Reduce the Energy Cost of Walking in Older Adults - Fausto Antonio Panizzolo; Eugenio Annese; Antonio Paoli; Giuseppe Marcolin (Applied Sciences, 2021)
Difficulty walking in older adults affects their independence and ability to execute daily tasks in an autonomous way, which can result in a negative effect to their health status and risk of morbidity. Very often, reduced walking speed in older adults is caused by an elevated metabolic energy cost. Passive exoskeletons have been shown to offer a promising solution for lowering the energy cost of walking, and their simplicity could favor their use in real world settings. The goal of this study was to assess if a constant and consistent low torque applied by means of a passive exoskeleton to the hip flexors during walking could provide higher and more consistent metabolic cost reduction than previously achieved. Eight older adults walked on a treadmill at a constant speed of 1.1 m/s with and without the hip assistive device. Metabolic power and spatiotemporal parameters were measured during walking in these two conditions of testing. The hip assistive device was able to apply a low torque which initiates its assistive effect at mid-stance. This reduced the metabolic cost of walking across all the participants with respect to free walking (−4.2 ± 1.9%; p = 0.002). There were no differences in the spatiotemporal parameters reported. This study strengthened the evidence that passive assistive devices can be a valuable tool to reduce metabolic cost of walking in older adults. These findings highlighted the importance of investigating torque profiles to improve the performance provided by a hip assistive device. The simplicity and usability of a system of this kind can make it a suitable candidate for improving older adults’ independence.